2020
DOI: 10.31557/apjcp.2020.21.6.1787
|View full text |Cite
|
Sign up to set email alerts
|

Risk Scoring System based on lncRNA Expression for Predicting Survival in Hepatocellular Carcinoma with Cirrhosis

Abstract: Objective: This study aims to explore the roles of long non-coding RNAs (lncRNAs) for predicting survival in hepatocellular carcinoma (HCC) patients with cirrhosis. Methods: A set of lncRNAs differentially expressed between HCC patients with or without cirrhosis was identified using expression profiles of The Cancer Genome Atlas database, and these lncRNAs were screened for their risk scoring system to predict recurrence-free survival (RFS) or overall survival (OS). Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Among these selected ILRPs, the roles of several irlncRNAs have previously been investigated in some cancers. Ye et al indicated that AC136475.3 can serve as a prognostic biomarker for patients with HCC who have cirrhosis (27). HOXB-AS3 has a dual role in various cancers; in colon cancer, it acts as a tumor suppressor, but in lung cancer, it acts as a tumor promoter (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Among these selected ILRPs, the roles of several irlncRNAs have previously been investigated in some cancers. Ye et al indicated that AC136475.3 can serve as a prognostic biomarker for patients with HCC who have cirrhosis (27). HOXB-AS3 has a dual role in various cancers; in colon cancer, it acts as a tumor suppressor, but in lung cancer, it acts as a tumor promoter (28,29).…”
Section: Discussionmentioning
confidence: 99%
“… 21 Additionally, LINC00239 is identified as a biomarker to predict the overall survival of patients with hepatocellular carcinoma without fibrosis. 40 However, the expression and functions of LINC00239 in CRC are poorly understood. In this study, LINC00239 was found to be overexpressed in CRC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are numerous studies on the relationship between MRPs and digestive tract cancer, some of the explorations have been done in the last 5 years. As mentioned above, MRPL23 not only promotes the metastasis of salivary adenoid cystic carcinoma, it is also related to the occurrence of liver cancer [ 112 ], suggesting that the same MRP can affect different cancers. However, it is not clear whether there is a difference in the mechanism of its influence.…”
Section: Mrps Associated With Cancersmentioning
confidence: 99%